1998
DOI: 10.1080/00288233.1998.9513311
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cattle treading on hill land: 1. Soil damage patterns and pasture status

Abstract: An experiment was conducted on steep hill land in New Zealand to describe the pattern of cattle treading that occurred from a single damage event during winter. The experiment also measured some of the consequences of treading and sought to define the subsequent grazing management which promoted the most rapid recovery of pasture.In hill paddocks of mixed topography, damage of the soil surface was greatest on animal tracks/ camps and easy contoured areas (<25°) where cattle prefer to walk. Evidence of this ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 14 publications
(22 reference statements)
2
40
1
Order By: Relevance
“…The soil is predominantly Waingaro steepland soil, a northern yellow-brown earth (Umbric Dystrochrept, USDA Soil Taxonomy), derived from a sedimentary greywacke parent material (Bruce 1978 a shallow (5-7.5 cm depth) clay loam topsoil of fine and medium nut structure, and a subsoil of firm clay with a weakly developed nut structure (Bruce 1978). Additionally, the soil has medium liquid and plastic limits of 57 and 49% (on a gravimetric basis) respectively, suggesting sensitivity to changes in soil moisture (Fieldes 1968a,b;Sheath & Carlson 1998). The riparian wetland site (PW5) selected for this study is c. 350 m 2 (0.35 ha), located near the base of an ephemeral stream channel that drains a steep (10-30°) catchment (1.3 ha) and an upland wetland, just up stream from the location of its discharge into the Mangaotama River.…”
Section: Study Sitementioning
confidence: 99%
“…The soil is predominantly Waingaro steepland soil, a northern yellow-brown earth (Umbric Dystrochrept, USDA Soil Taxonomy), derived from a sedimentary greywacke parent material (Bruce 1978 a shallow (5-7.5 cm depth) clay loam topsoil of fine and medium nut structure, and a subsoil of firm clay with a weakly developed nut structure (Bruce 1978). Additionally, the soil has medium liquid and plastic limits of 57 and 49% (on a gravimetric basis) respectively, suggesting sensitivity to changes in soil moisture (Fieldes 1968a,b;Sheath & Carlson 1998). The riparian wetland site (PW5) selected for this study is c. 350 m 2 (0.35 ha), located near the base of an ephemeral stream channel that drains a steep (10-30°) catchment (1.3 ha) and an upland wetland, just up stream from the location of its discharge into the Mangaotama River.…”
Section: Study Sitementioning
confidence: 99%
“…Additionally, as slope degree increases less water enters the soil and more runs off as overland flow. In this situation, when grazing pressure increases in mountain pastures, soils will be susceptible to degradation from processes such as runoff and erosion (Sheatch et al, 1998). In mountainous areas, significant variations in soil texture in relation to topography have been reported both in Mediterranean basin (Badano et Soil pH is considered to be an important factor that determines the floristic diversity and composition of grasslands (Critchley et al, 2002).…”
Section: Slope Degree and Soil Propertiesmentioning
confidence: 99%
“…Secondly it has been found that sheep follow particular pathways, concentrating the hoof pressures on a small area of the fields (Sheath and Carlson, 1998;Gilman, 2002).…”
Section: Buffer Stripsmentioning
confidence: 99%